Spatial variations in soil hydraulic conductivity in a Guarani Aquifer System recharge area - Rocha, Rodrigo Esteves [UNESP]; Gastmans, Didier [UNESP]; Sacchi, Marcelo Donadelli [UNESP]; De Oliveira, Marcelo Dias [UNESP] (Instituto Geologico, 2019)
Data on the hydraulic conductivity of soils are important for the understanding of water infiltration processes, and contribute to reduce uncertainties in water balance estimation in watersheds. These data not only allow a better understanding of the spatial distribution of recharge rates in unconfined aquifers, but also are used to develop strategies for the rational and integrated use of surface water and groundwater. In this regard, the objective of this study was to determine the spatial variability of the hydraulic conductivity in a watershed and compare the observed variations with physiographic and geological aspects. The study area is located in the upper portion of the Jacaré-Pepira sub-basin, an important recharge area of the Guarani Aquifer System (GAS). The hydraulic conductivity was measured using a Guelph Permeameter, which allows the measurement of the recharge under constant hydraulic head, responsible for maintaining the hydraulic head in a saborehole in the ground. The hydraulic conductivity of soils in the study area varied from 1.99E-6 to 6.02E-2 cm s-1, with the highest values associated with sandy soils derived from sandstones of the Botucatu and Piramboia formations, and the lowest ones associated with clayey soils formed by weathering of basaltic rocks from the Serra Geral Formation. A map of hydraulic conductivity distribution of the watershed was created with data measured in the study area. Visual comparison between this map and the geological map of the area corroborated the strong correlation between the hydraulic conductivity and the lithology. Therefore, the variability of the hydraulic conductivity is essentially controlled by outcropping lithologies and their position in the relief.
Variações espaciais na condutividade hidráulica do solo em área de recarga do Sistema Aquífero Guarani
Keywords: Guarani aquifer system; Guelph permeameter; Recharge; Small watershed